Study of combining ability of meadow clover varieties for breeding purposes in the conditions of the Volga-Vyatka region - E. G. Arzamasova; E. V. Popova; M. N. Gripas' (Аграрная наука Евро-Северо-Востока)
The article presents the results of research work on the assessment of general combining ability (GCA) and specific combining ability (SCA) in 14 varieties of meadow clover (Trifolium pratense L.) of various ecological and geographical origin (Russia, Belarus). The study was aimed at identifying the best varieties according to productivity indicators for inclusion into the breeding process in the conditions of the Volga-Vyatka region. The study of initial cultivars and their hybrid forms F1 was carried out in the field experiment of 2009 with two-year use of grass stand (2010, 2011). The characteristics of cultivars according to the main morphological and biological characteristics (winter hardiness, length of the vegetative period, plant height, grass stand vigour) and economically significant indicators (collection of raw and dry phytomass, seed yield) in comparison with the zoned Dymkovsky variety are given. All varieties showed high winter hardiness in the conditions of the Kirov region (more than 79 %). By productivity of green mass the varieties Karmin, Trio, Stodolich (Russia) were selected. They provided significantly high productivity for 2 years of grass stand use (5.52-5.81 kg/m2, +2.01-2.30 kg/m2 to standard) and were characterized by medium value of GCA (104.2-109.6 %) and very high SCA (123.7-139.3 %). According to the total collection of dry phytomass, the best varieties were Karmin and Gefest (Russia) with a significantly high level of productivity (1.28; 1.29 kg/m2, +0.49; 0.50 kg/m2 to standard), medium GCA (102.4; 103.2 %) and very high SCA (133.3; 134.4 %). By seed yield, the most productive Russian varieties are Stodolishchensky, Trio and Svetlyachok (74.2-82.6 g/m2, +8.8-17.2 g/m2 to standard) with very high GCA (125.5-139.8 %) and SCA value of medium and high level (106.6-118.7 %). According to the results of the study, for further breeding work the following meadow clover cultivars of Russian research institutes breeding were included as components of new polycross populations: early-matured Karmin and Trio, late-matured Gefest and Svetlyachok.